MPPT Based on Fuzzy Logic Controller (FLC) for Photovoltaic (PV) System in Solar Car - Seno Aji; Dwi Ajiatmo; Imam Robandi; Heri Suryoatmojo (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2013)
This paper presents a control called Maximum Power Point Tracking (MPPT) for photovoltaic (PV) system in a solar car. The main purpose of this system is to extracts PV power maximally while keeping small losses using a simple design of converter. Working principle of MPPT based fuzzy logic controller (MPPT-FLC) is to get desirable values of reference current and voltage. MPPT-FLC compares them with the values of the PV's actual current and voltage to control duty cycle value. Then the duty cycle value is used to adjust the angle of ignition switch (MOSFET gate) on the Boost converter. The proposed method was shown through simulation performed using PSIM and MATLAB software. Simulation results show that the system is able to improve the PV power extraction efficiency significantly by approximately 98% of PV’s power.